If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(8v + -7) = 25 + -5v Reorder the terms: -1(-7 + 8v) = 25 + -5v (-7 * -1 + 8v * -1) = 25 + -5v (7 + -8v) = 25 + -5v Solving 7 + -8v = 25 + -5v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '5v' to each side of the equation. 7 + -8v + 5v = 25 + -5v + 5v Combine like terms: -8v + 5v = -3v 7 + -3v = 25 + -5v + 5v Combine like terms: -5v + 5v = 0 7 + -3v = 25 + 0 7 + -3v = 25 Add '-7' to each side of the equation. 7 + -7 + -3v = 25 + -7 Combine like terms: 7 + -7 = 0 0 + -3v = 25 + -7 -3v = 25 + -7 Combine like terms: 25 + -7 = 18 -3v = 18 Divide each side by '-3'. v = -6 Simplifying v = -6
| -7f=56 | | (7x+1)(8x-6)= | | x+7=3x+9.5 | | (x^(2/3)y^(-(5/4)))^6 | | 1.4/7.7 | | lg(x^2-x-6)-lg(x-3)=0 | | 25x^2+35x=0 | | 5=-7+a | | 40=-8(x+2) | | 1.5y-2=y | | 1/2x+2/5=1/3x+3/4 | | 10*t+6*(0.8-t)=6 | | (x-16)2=64 | | 9x+20=2x+125 | | 4x-6=x-18 | | -5k-2+9k+6= | | 1/2(6x-4)-4x=3x-18 | | x^4+18x^2+17=0 | | 3x-x+1=2x+5 | | 7=n+5 | | x*x+25=10x | | 9n+7n-5-4= | | 4x-5y+3z= | | .75(4-8x)=0.8(5+10x)+1 | | a(3a-2)+2a(a+4)=a(a+2) | | Ln(x-15)=10 | | 4x-6-3x= | | S=4rt | | (3x^2+5)(2x^5-1)= | | 11x-20=7x+7 | | 2204.28=2(3.14(13)(13))+2(3.14(13)(h)) | | 18=5y-7 |